Analyse der Bestäubernetzwerke im Kümmel (Carum carvi) mittels DNA-Barcoding - Killian Salas, Isabel C.; Hamm, Andrée; Mengual, Ximo; Peters, Ralph; Wägele, Wolfgang (Julius-Kühn-Archiv, 2018)
Insect pollination is one of the most important ecosystem services provided to humans. Over 75% of crops and 87,5% of wild plants are directly dependend from this type of pollination. The two biggest insect pollination groups in German agroecosystems are the Brachycera (“true flies”) and Hymenoptera. However, a decline trend in agricultural biodiversity has been observed in the past years, which is why the need for sustainable conservation strategies for pollination services is more needed than ever before. Therefore, via DNA-Barcoding the potential pollinators of caraway (Carum carvi) will be identified. Additionally, other plants that might be important in the pollination network of caraway will be identified via Metabarcoding pollen samples. Therefore, Hymenoptera and Brachycera samples were collected during the vegetations periods of 2016 and 2017 on two areas (one with and one without flowering strips) with a hand net on three different day intervals. Overall, on 14 sampling days of each year pollinators were collected, and in 2016 in total 1055 specimens were compiled. First preliminary results of morphological and genetic analysis suggest that around 54 fly and 43 Hymenoptera species are present in the caraway before, during and after the blooming. Further aims are to combine these results with the one of the metabacoding, build up the pollinator network of caraway, and based on this information generate future recommendations for a sustainable management of pollination services.